Monte Carlo simulation of the cosmic muon charge ratio - Abd Al Karim Haj Ismail (Kuwait Journal of Science)
The muonic component of air showers is sensitive to the mass and energy of the primary cosmic ray and is the most abundant component of charged particles arriving at the surface, and able to penetrate deeply underground. The muon charge ratio, defined as the number of positive over negative charged muons, is a very interesting quantity for the study of hadronic interactions at high energies and the nature of cosmic ray primaries. Furthermore, Earth's atmosphere is the development medium of cosmic air showers before they arrive at the ground. Therefore, variations in the density of the atmosphere between seasons must be studied. It is also very important to account for the zenith angular dependence of atmospheric muons, in particular for showers penetrating the atmosphere at high zenith angles.